IMPLEMENTASI MANAJEMEN SUMBER DAYA TENAGA KEPENDIDIKAN DALAM MENINGKATKAN KUALITAS LAYANAN PENDIDIKAN - dahliah (UNISAN JURNAL, 2024)
The role of human resources in business is as a company’s internal driving force that utilizes all facilities within the company to achieve goals. Good human resources will be able to achieve maximum results if they are managed in a planned, organized, controlled, supervised manner and supported by accuracy in motivating. Placing someone according to their expertise is one of the characteristics of Islamic professionalism. The Prophet and his companions truly implemented these noble values ​​in their leadership. Public service management is the regulation of the implementation of all forms of services carried out by government officials on behalf of institutions to meet the needs of the community by paying attention to the essence of the service. Based on research regarding the role of human resources in improving the quality of services in education, it shows that the role of human resources is quite optimal in improving the quality of services at SMP IT Insan Taqwa. Empowerment or Empowerment through work positions with employee expertise has gone well because the employees have been placed appropriately. with the skills you have. Keywords: Resource Management, Education Services